PROFIL PNEUMONIA NEONATUS YANG DIRAWAT DI RSUP PROF. Dr. R. D. KANDOU MANADO - Jufri, Juhtisari; Wahani, Audrey; Wilar, Rocky (Universitas Sam Ratulangi, 2013)
Abstrack: Background : Pneumonia is an important cause of neonatal infection. Neonatal mortality rate in pneumonia ranged from 750,000 to 1.2 million deaths and the number of deaths is unknown at birth each year. Methods : This study uses a retrospective descriptive. Results : 95.31% occurred in the age group 0-7 days. 85.94% with normal leukocyte levels. 54.69% trombist normal levels. 40.62% increase hemoglobin levels. On examination CRP increased 67.86%. 54.69% IT ratio <0.2. 96.87% with clinical symptoms of tachypnea. 45.83% using the first linea (amoxycillin + gentamicin). 53.12% of patients were healed with the state. Conclusions : Neonatal pneumonia is most prevalent in early onset (0-7 days). Normal leukocytes are most found. While the platelets also found in most normal limits. The hemoglobin most commonly found an increase. Examination results are most CRP increased. Furthermore, the examination and the ratio of immature neutrophils total (IT ratio) is most commonly found <0.2. Tachypnea is the most clinical symptoms found. Patients with pneumonia were cured many neonates using the first linea treatment combinations (amoxycillin + gentasmisin). Mortality rates were obtained from neonates suffering from pneumonia at 4.69%. Key words : Pneumonia, neonates. Abstrak: Latar Belakang : Pneumonia merupakan penyebab penting infeksi neonatal. Angka kematian neonatal pada penyakit pneumonia berkisar antara 750.000 sampai 1,2 juta kematian dan jumlah kematian saat dilahirkan tidak diketahui setiap tahunnya. Metode : Penelitian ini menggunakan metode deskriptif retrospektif. Hasil : 95,31 % terjadi pada kelompok umur 0 – 7 hari. 85,94 % dengan kadar leukosit normal. 54,69 % kadar trombist normal. 40,62 % kadar hemoglobin meningkat. Pada pemeriksaan CRP 67,86 % meningkat. 54,69 % IT Rasionya <0,2. 96,87 % dengan gejala klinis takipnea. 45,83 % menggunakan linea pertama (amoxycillin+gentamisin). 53,12 % dengan keadaan penderita yang sembuh. Kesimpulan : Pneumonia neonatus paling banyak ditemukan pada onset awal (0-7 hari). Leukosit ditemukan paling banyak normal. Sementara trombosit juga ditemukan paling banyak dalam batas normal. Hemoglobin paling banyak ditemukan adanya peningkatan. Pemeriksaan CRP hasilnya paling banyak mengalami peningkatan. Selanjutnya pada pemeriksaan Rasio imatur dan neutrofil total (Rasio IT) yang paling banyak ditemukan <0,2. Takipnea merupakan gejala klinis yang paling banyak ditemukan. Penderita pneumonia neonatus banyak yang sembuh dengan menggunakan pengobatan linea pertama kombinasi (amoxycillin+gentasmisin). Angka kematian yang didapatkan dari neonatus yang menderita pneumonia sebesar 4,69%. Kata Kunci : Pneumonia, neonatus.